2014
DOI: 10.1038/ja.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Helicobacter pylori to tetracycline, amoxicillin, clarithromycin and metronidazole in Israeli children and adults

Abstract: The aim of this study was to examine Helicobacter pylori-resistance rate to different antibiotics: tetracycline, amoxicillin, clarithromycin and metronidazole, and to compare eradication rates in adults and children in Israel. The study was based on the hypothesis of high-resistance rates to clarithromycin and metronidazole especially in adults and overall low-resistance rates to tetracycline and amoxicillin. One seventy six biopsies from patients with dyspeptic symptoms were cultured of which 100 were from ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
5
14
0
1
Order By: Relevance
“…In addition, resistance rate to clarithromycin has increased, and is 3 times higher (similar rates in both methods) in comparison to data published earlier in Israel, in accordance with the global increasing trend [19]. A possible explanation for a lower resistance rate to fluoroquinolones in comparison to clarithromycin could be due to its later addition to treatment protocols of H. pylori infection.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, resistance rate to clarithromycin has increased, and is 3 times higher (similar rates in both methods) in comparison to data published earlier in Israel, in accordance with the global increasing trend [19]. A possible explanation for a lower resistance rate to fluoroquinolones in comparison to clarithromycin could be due to its later addition to treatment protocols of H. pylori infection.…”
Section: Discussionsupporting
confidence: 65%
“…Peretz et al [13] found that 22.3% of H. pylori isolates from treatment naĂŻve adults in 2011–2012 were resistant to clarithromycin. Zevit et al [16] found a rate of clarithromycin resistance of 25% among untreated children.…”
Section: Discussionmentioning
confidence: 99%
“…A high resistance was also found among the strains isolated from children in Poland (33.3% were resistant to CH, 44.8% to MZ, whereas 1.9% of strains were resistant simultaneously to CH, MZ, and levofloxacine (LEV) . An unusually high resistance for amoxicillin (12.2%) was found in Israeli children . In a Japanese study between 2000 and 2013, among 1073 H. pylori‐ positive patients of different ages, the rate of clarithromycin resistance was extremely high (57.9%) in those under the age of 31 years .…”
Section: Diagnosismentioning
confidence: 99%